1994
DOI: 10.1038/372270a0
|View full text |Cite
|
Sign up to set email alerts
|

Operons as a common form of chromosomal organization in C. elegans

Abstract: Although eukaryotic genes are usually transcribed individually, at least a few Caenorhabditis elegans genes appear to be transcribed polycistronically in clusters resembling bacterial operons. The spliced leader SL2 (ref. 2) is specific for trans-splicing to downstream genes in these operons. In addition, many C. elegans pre-mRNAs are trans-spliced to SL1 (ref. 3) near the 5' ends of pre-mRNAs. Because operons have not previously been found in higher eukaryotes, we have investigated how widespread they are in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
227
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(237 citation statements)
references
References 17 publications
9
227
1
Order By: Relevance
“…Hence, full-length end-1 transcripts start at or very close to this position. They appear not to be trans-spliced, as was further confirmed by RT-PCR analysis using primers specific for the SL1 and SL2 leaders (Krause and Hirsh 1987;Bektesh et al 1988;Zorio et al 1994) (data not shown).…”
Section: Sequencing Of the End-1 Clone And 5ј End Determinationmentioning
confidence: 76%
“…Hence, full-length end-1 transcripts start at or very close to this position. They appear not to be trans-spliced, as was further confirmed by RT-PCR analysis using primers specific for the SL1 and SL2 leaders (Krause and Hirsh 1987;Bektesh et al 1988;Zorio et al 1994) (data not shown).…”
Section: Sequencing Of the End-1 Clone And 5ј End Determinationmentioning
confidence: 76%
“…Since the snRNP E and clpP gene products are not known to be functionally related, the dicistronic transcription is unlikely to represent an ancient operon in the classic prokaryotic sense. Rather, it appears more likely to have arisen de novo during genome compression, as has been suggested for the polycistronic gene clusters in Caenorhabditis elegans (20). The possibility that other nucleomorph genes could also be cotranscribed is currently being examined (e.g., clpP and RNA polymerase subunit).…”
mentioning
confidence: 99%
“…We are currently examining whether the dicistronic message is translated in tandem (21) or undergoes further processing, perhaps to insinuate a trans-spliced leader ahead of the downstream ORF, as shown for the polycistronic messages of C. elegans (20).…”
mentioning
confidence: 99%
“…In higher eukaryotes, mRNA 39 end formation is dependent on a complex of proteins including cleavage and polyadenylation specificity factor (CPSF) and cleavage stimulatory factor (CstF)+ CPSF binds to the AAUAAA signal just upstream of the site of 39 end formation, whereas CstF binds to a U-rich or GU-rich signal about 30 bp downstream of the 39 end formation site (reviewed in Zhao et al+, 1999)+ In vertebrates, the upstream site is nearly always a perfect AAUAAA, but in Caenorhabditis elegans, a number of variants occur (Blumenthal & Steward, 1997)+ One rare variant, AGUAAA, used in ,1% of C. elegans genes, is present at the 39 end of the mai-1 gene (Lee et al+, 1992)+ Utilization of this rare variant is conserved in the mai-1 gene of Caenorhabditis briggsae, a species that diverged from C. elegans about 50 million years ago, so it is likely to be functionally significant+ Some of the mai-1 mRNA is cleaved and polyadenylated immediately following the AGUAAA, but much of it extends an additional 100 nt downstream (Spieth et al+, 1993), suggesting the AGUAAA could result in inefficient 39-end formation+ Both mRNAs clearly represent sites of polyadenylation, as both classes are represented in an oligo(dT)-primed cDNA library (Spieth et al+, 1993)+ In C. elegans, many genes are arranged in operons (Spieth et al+, 1993;Zorio et al+, 1994)+ These closely clustered genes are cotranscribed to produce polycistronic pre-mRNAs that are processed into mature monocistronic transcripts+ This involves a combination of cleavage and polyadenylation at the 39 end of the upstream mRNA and trans-splicing at the 59 end of the downstream mRNA+ In trans-splicing, a 22-nt spliced leader (SL) is transferred from the SL snRNP to the 59 ends of the mRNAs (reviewed in Blumenthal & Steward, 1997)+ The major spliced leader, SL1, is used when the trans-splice site is close to the 59 end of the premRNA+ A second type of SL RNP, SL2, is used exclusively for trans-splicing to the downstream genes in polycistronic transcripts+ However, some downstream genes in operons are trans-spliced to both SL1 and SL2 (Blumenthal & Steward, 1997)+ mai-1 is the first gene in a three-gene operon, and the gene following mai-1, gpd-2, is trans-spliced mostly to SL1 (Huang & Hirsh, 1989;Spieth et al+, 1993)+ Because genes in operons are separated by about 100-400 bp, it is possible that 39-end formation at the upstream gene and trans-splicing at the 59 end of the downstream gene are functionally coupled+ Indeed, elimination of 39-end formation of an upstream gene reduced the level of SL2 trans-splicing to the gpd-3 trans-splice site 110 nt downstream (Kuersten et al+, 1997)+ Here we test the idea that the rare AAUAAA variant present at the 39 end of mai-1 results in inefficient 39-end formation and in the utilization of SL1 instead of SL2+ We demonstrate that by changing the signal to a perfect AAUAAA, both 39-end formation efficiency at the proximal site and SL2 trans-splicing of gpd-2 increase+ We also demonstrate that 39-end formation at the distal site is dependent on the transsplice site, but not the AGUAAA 100 bp upstream, suggesting the existence of a novel mechanism of 39-end formation in C. elegans operons+…”
Section: Introductionmentioning
confidence: 99%